SPE International Symposium on Oilfield Chemistry 2001
DOI: 10.2118/65394-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brine Composition and Alkaline Fluid on the Permeability Damage of Limestone Reservoirs

Abstract: Secondary and tertiary recovery processes can lead to severe and permenant reductions in permeability because of interactions between injected fluids and the reservoir rock. Permeability damage was suspected as a factor contributing to post completion production declines observed during waterflooding of an unconsolidated limestone.This study summarizes the laboratory studies undertaken to evaluate and understand permeability damage in limestone reservoirs. The influence of brine composition, salinity of alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is used to describe the salinity at which the lowest oil/water IFT is achieved during alkaline and/or surfactant flooding. Bagci et al (2001) reported that the IFT decreased and then increased with increasing salinity of NaOH and NaSiO 4 brines. The dilution of synthetic reservoir brine at ambient conditions also showed a decreasing and then increasing trend in IFT (Vijapurapu and Rao 2004), and the minimum IFT fell below Zisman-type critical spreading tension, resulting in the spreading of oil on the solid surface displacing brine.…”
Section: Effect Of Brine Composition On Iftmentioning
confidence: 99%
“…It is used to describe the salinity at which the lowest oil/water IFT is achieved during alkaline and/or surfactant flooding. Bagci et al (2001) reported that the IFT decreased and then increased with increasing salinity of NaOH and NaSiO 4 brines. The dilution of synthetic reservoir brine at ambient conditions also showed a decreasing and then increasing trend in IFT (Vijapurapu and Rao 2004), and the minimum IFT fell below Zisman-type critical spreading tension, resulting in the spreading of oil on the solid surface displacing brine.…”
Section: Effect Of Brine Composition On Iftmentioning
confidence: 99%
“…The permeability reduction of shale samples and its effect on gas well production have attracted much attention in recent years. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]32 Song et al 33 evaluated the influence of polymer on the permeability reduction to gas and water by using shale fracture models with different fracture widths. The polymer resisted gas flow less than water flow in the microfracture.…”
Section: Introductionmentioning
confidence: 99%